Pengaruh Sistem Finansial Pendidikan Terhadap Mutu Lulusan di SMK Swastaabdi Nusantara Sei Bamban Kecamatan Sei Bamban - Budi Suhartono; Rini Dewi Andriani; Achmad Zaki (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2021)
This study aims to determine the effect of the financial system of lipering the quality of graduates in the Abdi Nusantara Sei Bamban Vocational School, Sei Rampah District, Serdang Bedagai Regency. The method used in data collection of researchers is to carry out activities to encounter research respondents and ask them to fill in the research questionnaire (questionnaire refers to the Likert scale). The results of the study there was a significant influence of the financial education system on the quality of graduates in the Private Vocational School Abdi Nusantara Sei Bamban Sei Bamban sub-district with a correlation value of 0.851 meaning that the financial system of education has a correlation of the quality of graduates at ABDI Nusantara Sei Bamban Sei Rampah Subdistrict, Sei Rampah Regency, Bedagai. Enough or 72.35%.